Does Maternal Body Mass Index Influence Treatment Effect in Women with Mild Gestational Diabetes? - Casey, Brian M.; Mele, Lisa; Landon, Mark B.; Spong, Catherine Y.; Ramin, Susan M.; Wapner, Ronald J.; Varner, Michael W.; Rouse, Dwight J.; Thorp, John M., Jr.; Catalano, Patrick; Harper, Margaret; Saade, George; Sorokin, Yoram; Peaceman, Alan M.; for the National Institute of Child Health and Human Development Maternal-Fetal Medicine Units Network (American Journal of Perinatology, 2015)
Objective The aim of the article is to determine whether maternal body mass index (BMI) influences the beneficial effects of diabetes treatment in women with gestational diabetes mellitus (GDM).Study Design Secondary analysis of a multicenter randomized treatment trial of women with GDM. Outcomes of interest were elevated umbilical cord c-peptide levels (> 90th percentile 1.77 ng/mL), large for gestational age (LGA) birth weight (> 90th percentile), and neonatal fat mass (g). Women were grouped into five BMI categories adapted from the World Health Organization International Classification of normal, overweight, and obese adults. Outcomes were analyzed according to treatment group assignment.Results A total of 958 women were enrolled (485 treated and 473 controls). Maternal BMI at enrollment was not related to umbilical cord c-peptide levels. However, treatment of women in the overweight, Class I, and Class II obese categories was associated with a reduction in both LGA birth weight and neonatal fat mass. Neither measure of excess fetal growth was reduced with treatment in normal weight (BMI < 25 kg/m2) or Class III (BMI ≥ 40 kg/m2) obese women.Conclusion There was a beneficial effect of treatment on fetal growth in women with mild GDM who were overweight or Class I and Class II obese. These effects were not apparent for normal weight and very obese women.
Keywords: gestational diabetes; BMI; treatment effect